Social exclusion - Byrne, D. S. (David S.), 1947- (Issues in society., 2005)
"The second edition of this widely read book explores developments in social theory, social experience and social policy in relation of Social Exclusion. The first part examines the origins of the term and implications of the difference between the ideas of 'exclusion', 'underclass', 'residuum' and related concepts. The discussion is informed by the application of Complexity Theory. In the updated second part, the theoretical account in developed through a detailed review of the dynamics of individual lives in a changing social order. Income equality, spatial division, and exclusion in relation to health, education and cultural provision and processes are examined in a range of societies in Europe and North America." "The last part contains a new chapter outlining the content and impact of national and international policies which have been specifically developed to address issues of exclusion. This is important reading the students on social sciences courses including sociology, social theory and social policy."--Jacket